(untitled) (Scientific journal of the Fergana State University, 2024)
The article is devoted to the study of the influence of foreign compounds on the process of transfer of natural solar radiation entering the layers of the atmosphere into the layers of the atmosphere. The influence of foreign compounds (aerosol particles) entering the atmosphere on the formation of diffuse-return and diffuse-non-scattered flows from the atmosphere is shown. Calculations were carried out on the basis of Chanrasekhar’s theory of -functions, and the values of these functions were determined by the factorization method.